(3ebGdI aj GdTcd GdQGHY ef CTcGd GdbjGS GdMedi hgh GdefShH Edi LGdjfhSs - (3CHh GdaJhM fLe GdOjf CMeO Hf eMeO Hf GdSQj GdHZOGOj, GHf GdUdGM,J (B548 (3g` s
(3ChdgG (B:s
(3EfG hLOfG Md GdefWbjjf dWQMhf gPG GdTcd hjdbhf PcQg MJi CfG fLO GdcJH GdcHGQ GdJi OhfJ ai TQM CfGdhWjbG GdChdi NGdjI Yf PcQg s
(3BNQgG (B:s
(3aEfg eMJGL Edi HjGf BNQ hdGf gPG Gdaf ef GdYde bO cGf GdbOeGA jaQRhfg Yf GdChd JeJ GdebGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs